Teaching Digital Archives Management Using Google Sites, Google Drive, and Gmail - Herawati, Elvina; Suwilo, Saib; Mawengkang, Herman; Syahmrani, Aghni (Talenta Publisher, 2023)
Study plans, study modules, practice questions and exams from teachers, results of student exercises and exams, photos and videos of teaching activities, and other teaching files for each subject are teaching data that can be used to obtain quality education. However, some of the data is not documented by Partners in a systematic and comprehensive manner. If the data is physically collected, it will require a repository for the data, so it will take time to organize the warehouse, search for files, and provide files to teachers or students who need the files. To keep teaching data collected without using physical storage warehouses, digital archiving can be used. Google Sites, Google Drive, and Gmail can be used to build digital archives. The USU Mathematics Master’s Program team plans to build a site through Google Sites to archive digital files and to display digital archives that are stored on Google Drive and which can be submitted via Gmail online. In addition, the Team also provides training for Partners to build and develop sites on Google Sites and perform digital archive management on Google Drive and integrate Google Sites and Google Drive with Gmail.